2021
DOI: 10.1007/s40199-021-00390-z
|View full text |Cite
|
Sign up to set email alerts
|

Surging trends in prescriptions and costs of antidepressants in England amid COVID-19

Abstract: The social restrictions amid coronavirus disease 2019 (COVID-19) pandemic have posed a serious threat to mental health and have implications in the use of medications for mental health including antidepressants (ADs). This study investigated the trends in prescriptions and costs of various ADs in England during COVID-19 pandemic. National prescribing rates and net ingredient costs (NIC) of all ADs prescriptions during 2016 to 2020 were analyed. The total number of ADs prescriptions dispensed during COVID-19 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 24 publications
5
53
2
4
Order By: Relevance
“…The analysis of the pharmacological treatment showed a higher antidepressant consumption in the group without prior COVID-19. The COVID-19 pandemic has led to an increase in the incidence of depression, so the use of antidepressants has increased, and this has been surprisingly linked to protection against SARS-CoV-2 [ 22 , 23 ]. The mechanism of this association is unclear, but it could be suspected that some antidepressants functionally inhibit acid sphingomyelinase activity (ASM), and in cell culture models, inhibition of ASM prevents the infection of cells with SARS-CoV-2 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the pharmacological treatment showed a higher antidepressant consumption in the group without prior COVID-19. The COVID-19 pandemic has led to an increase in the incidence of depression, so the use of antidepressants has increased, and this has been surprisingly linked to protection against SARS-CoV-2 [ 22 , 23 ]. The mechanism of this association is unclear, but it could be suspected that some antidepressants functionally inhibit acid sphingomyelinase activity (ASM), and in cell culture models, inhibition of ASM prevents the infection of cells with SARS-CoV-2 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that used antidepressants drugs as preventive treatments [ 22 , 25 , 26 ] have not reported similar results to us. We consider this topic interesting due to increase of mental illness associated with the COVID-19 pandemic [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, population-based studies in various countries have demonstrated a significant increase in the incidence of mood disorders, prescriptions for antidepressants, and suicide ideation and attempts since the initiation of lockdowns and restrictions. With the surging rate of antidepressant prescriptions, it can be anticipated that there will also be an increase in observed common and uncommon adverse reactions associated with these medications, highlighting the need for continued reporting of rare adverse reactions [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a significant increase in pharmacotherapy treatment for anxiety and depression during the pandemic, with numerous jurisdictions indicating that anxiolytic and antidepressant use is at an all-time high. 16 With restrictions on social gatherings, feelings of isolation and helplessness are very common which negatively impact mental health, similarly, personal relationships are increasingly under strain during the pandemic. 17 Difficulty sleeping is a key indicator of anxiety and stress, among other factors.…”
Section: Discussionmentioning
confidence: 99%